Virunga National Park - Steder og rettigheder for gorillaer og mennesker i Afrika - Andersen, Frits (K&K - Kultur og Klasse, 2015)
The article outlines some of the historical traces for the eco-crisis that presently threatens the first and most outstanding national park in Africa, homeland of the mountain gorilla. After a short description of the site, the article presents the Congo Reform Movement’s campaign against the bloody suppression in the Congo Free State around 1900, often referred to as the Red Rubber-regime. The Congo Reform Movements “Atrocity Meetings” are considered to be the first human rights campaign, because they established the rhetorical models that we find today in Amnesty International, Human Rights Watch and Global Witness. The article argues that we can detect similar and highly problematic structures in the animal rights campaigns which took on a global scale in the 1970s – initiated among others by Dian Fossey and her famous and infamous fight for the protection of mountain gorillas in the Virunga mountains. Both human rights campaigns and animal rights campaigns share a responsibility, I argue, for the eco-crisis at Virunga. Finally I present the documentary Virunga from 2014 as a model and as a rhetorical alternative.